DESA VOKASI MENUJU KEMANDIRIAN EKONOMI MASYARAKAT (Studi Kasus Di Desa Vokasi Kembang Kecamatan Pacitan Kabupaten Pacitan) - Wiwid Anang Subekti; Heru Siswanto; Maria Veronika Reosminingsih (JPUS: Jurnal Pendidikan Untuk Semua, 2020)
Vocational village is an area of vocational skills education intended to develop human resources to be able to produce products / services or other works of high economic value, are unique and have a comparative advantage by utilizing local potential. The purpose of the vocational village program is to help the community to have the provision of productive knowledge and skills that can be utilized to manage the potential of local resources so that they have value for themselves and the community, have entrepreneurial attitudes and behaviors that are in line with the values or rules that apply in regions as well as preserving and developing noble values of regional culture in order to support national development. This research explains how Vocational Village with batik making training program can create economic independence in the Flower Village. This study uses a qualitative approach, data collection using in-depth interview techniques, participant observation and documentation. Data were analyzed using data condensation, data presentation, and data verification techniques. The technique is used to look for data in Vocational Village research towards community economic independence. The results of the study showed that the existence of vocational villages with training programs in making batik showed a positive influence on the life of the Kembang Village community. the skills taught in training can be used by the community to support life in economic terms. Various positive influences have been felt by the Kembang Village community who participated in a training program that brought about the aspects of economic independence..